2004
DOI: 10.1074/jbc.m407576200
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Roles for Histone Acetylation in Human T Helper 1 Cell-specific Gene Expression

Abstract: To better understand the control of T helper (T H ) 1-expressed genes, we compared and contrasted acetylation and expression for three key genes, IFNG, TBET, and IL18RAP and found them to be distinctly regulated. The TBET and the IFNG genes, but not the IL18RAP gene, showed preferential acetylation of histones H3 and H4 during T H 1 differentiation. Analysis of acetylation of specific histone residues revealed that H3(Lys-9), H4(Lys-8), and H4(Lys-12) were preferentially modified in T H 1 cells, suggesting a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 46 publications
3
50
0
1
Order By: Relevance
“…Chung and colleagues found that the acetylation of histone H3K9 recruited NF-B inducing kinase to promoters of proinflammatory genes such as IL-6, IL-8, and COX-2 (41, 42). Morinobu et al showed that acetylation of histone H3K9, H3K8, and H4K12 contributes to the preferential induction of IFN-␥ and T-bet genes in T helper cells (43). These results support the hypothesis that acetylation of histones participates in the regulation of inflammatory responses.…”
Section: Discussionsupporting
confidence: 79%
“…Chung and colleagues found that the acetylation of histone H3K9 recruited NF-B inducing kinase to promoters of proinflammatory genes such as IL-6, IL-8, and COX-2 (41, 42). Morinobu et al showed that acetylation of histone H3K9, H3K8, and H4K12 contributes to the preferential induction of IFN-␥ and T-bet genes in T helper cells (43). These results support the hypothesis that acetylation of histones participates in the regulation of inflammatory responses.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, when Th2 cells are treated with HDI, the acetylation status of both genes is recovered even though their gene expression is not restored, suggesting a more complex mechanism involved in Th1/Th2 differentiation (Morinobu et al, 2004). A similar mechanism regulates the IL-4 gene locus in T-cell differentiation.…”
Section: Hdacs and Cytokines Involved In T-cell Differentiationmentioning
confidence: 88%
“…Subsequently, cells were expanded in a new flask for another 3 days with replenished IL-12 (Th1), IL-4 (Th2), and IL-21/TGF␤ (Th17) without any antibodies (30,31). Differentiation experiments were performed individually with naïve T cells from single blood donors.…”
Section: Methodsmentioning
confidence: 99%
“…Because our findings suggest a role for CREM␣ in transcriptional control of the IL17A gene, we analyzed CREM␣ involvement in T helper (Th) cell differentiation by addition of specific cytokines and antibodies priming toward a Th1 (IL-12 and anti-IL-4), Th2 (IL-4 and anti-IFN␥), and Th17 (TGF␤ and IL-21) cell fate decision (29,30). Compared with Th1 and Th2 conditions, CREM␣ binding to CRE site (Ϫ111/Ϫ104) was significantly increased in Th17 differentiated cells (Fig.…”
Section: B and C)mentioning
confidence: 99%